Performance evaluation of fixed and mobile relay in WiMAX system - Mumtaz, S.; Tu, L.T.; Sadeghi, R.; Gameiro, A. (Journal of Digital Information Management, 2010)
Future wireless communication systems are expected to provide more stable and higher data rate transmissions in the whole network. WiMAX is one of the technologies to cover diverse geographic regions. WiMAX covers the high dense urban areas and provide access over large geographic regions in remote rural area. However, in both scenarios it is challenging to cover the entire service area. In both cases relays are foreseen to extend the range of the BS and to increase the system throughput allowing for a cost-efficient deployment and service. As multi-hop/relay has complex interactions between the routing and medium access control decisions, the extent to which analytical expressions can be used to explore its benefits are limited. Consequently simulations tend to be the preferred way of assessing the performance of relays. In this paper, we explain, how to deploy fixed-relay and mobile relay by using computer simulation in WiMAX system and we consistently observed that the throughput is increased and the outage is decreased in the relay-augmented WiMAX network, which is converted to range extension without any capacity penalty, for the realistic range of values of the propagation and other system parameters investigated.
Keywords: Coverage area; Fixed relay; Throughput; WiMAX

A method of reduction of the microinstructions of synchronous digital systems - Al-Dahleh, M.Z.; Shehabat, I.M. (Journal of Digital Information Management, 2007)
In this paper, the author presents a method to synthesize the Algorithm State Machines (ASM) for synchronous digital systems using Combined Addressing. In This proposed method, the microinstructions are divided into subsets, and thus the Numbers of microinstructions are apparently minimized and the throughput time of the automation is reduced.
Keywords: Combined addressing; Digital systems; Microinstruction (MI); Synchronized systems; Throughput